FLUVASTATIN EFFECTS ON BLOOD CELL AGGREGATION IN PATIENTS WITH ARTERIAL HYPERTENSION AND DYSLIPIDEMIA - I. N. Medvedev; I. A. Skoryatina (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the effects of fluvastatin on the blood cell aggregation in patients with arterial hypertension (AH) and dyslipidemia (DLP).Material and methods. The main group (MG) included 32 middle-aged patients with Stage 1–2 AH (Risk 3) and Type IIb DLP. The control group (CG) included 26 healthy middle-aged people. All patients received fluvastatin (40 mg/d in the evening) and enalapril (10 mg twice per day). The assessment of clinical and laboratory parameters was performed at baseline, and after 4, 12, and 52 weeks of the therapy.Results. In MG patients, the disturbances of blood lipid profile and lipid component of blood cell membranes, together with activation of lipid peroxidation (LP) in blood cell membranes, was associated with an increased aggregation of erythrocytes, platelets, and leukocytes. The 52-week fluvastatin therapy somewhat improved blood lipid profile and reduced LP activity in both plasma and blood cells. However, these parameters failed to reach the levels observed in the CG. The one-year treatment with fluvastatin in the MG reduced, but not completely normalised the aggregation of erythrocytes, platelets, and leukocytes.Conclusion. Treating patients with AH and DLP with fluvastatin for one year significantly reduces, but not normalises blood cell aggregation.